Lock-up Provisions and Underpricing in Initial Public Offerings: Evidence from Finland, Sweden, and Denmark - Palo, Pietari (My University, 2023)
Initial Public Offerings (IPOs) stand as a crucial stage for companies and investors alike. Historically, IPOs have been characterized by the phenomenon of underpricing, a situation where shares are issued to the public at a price lower than their market value, which can be interpreted from the initial day returns. Underpricing is a well-established phenomenon in previous academic research, and it has been observed previously in all the major markets. Previous academic literature on the effect of lock-up provisions in underpricing is still disorganized and inconsistent. This research explores the IPO landscape of the small- and middle-sized companies in the Nordic region, with a specific focus on Finland, Sweden, and Denmark, seeking to unravel the relationship between underpricing, lock-up provisions, and following stock performance. Data collected directly from company prospectuses sheds light on the impact of lock-up ratios and lock-up periods for management and other shareholders. The findings of this study reveal that these factors have a significant impact on short-term underpricing, a discovery that deepens our understanding of IPOs in the Nordics. The results suggest that stricter lock-up provisions are associated with increased underpricing, raising questions about whether such provisions serve as signals of higher quality or risk. While the implications for long-term returns are somewhat less distinct, this research highlights the role of lock-up provisions in affecting the IPOs. By shedding light on these critical dynamics, this study offers valuable insights for investors, underwriters, and companies issuing IPOs, thereby contributing to the growing body of knowledge on IPOs, financial markets, and the role of lock-up provisions in this complex environment.
Keywords: Underpricing, Lock-up provisions